Determinant Factors Motivated Waqif to Donate Waqf - Thuba Jazil; Safirah Rofifah; Tita Nursyamsiah (El Barka, 2019)
Abstract: This study aimed to investigate the waqf motivation in carrying out waqf in Bogor City. Primary data and questionnaire techniques were used by distributing to 103 waqif respondents. Factors were grouped into 2 categories, internal and external. Internal factors were religiosity, waqf literacy, trustworthiness in waqf institutions, income & wealth. Meanwhile, external factors included performance efficiency, tax incentives, the role of government, and the role of scholars. The method used was path analysis for internal factors and multiple linear regression analysis for external factors using SPSS 21. The results showed that waqf literacy and trustworthiness affected religiosity and also to waqf motivation while income & wealth had no effect. The role of government and the role of scholars had a significant positive impact on waqf motivation, but the performance efficiency of the institution and tax incentive had no significant effect.